2017
DOI: 10.1038/labinvest.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA expression profiles reveal the involvement of miR-26a, miR-548l and miR-34a in hepatocellular carcinoma progression through regulation of ST3GAL5

Abstract: MicroRNAs (miRNAs) have key roles in comprehensive physiological and pathological processes by targeting specific genes through translational repression. Identification of miRNAs related to metastasis enables us to obtain better insight into cancer development. In the current study, we investigated the miRNA expressional profiles in the highly invasive human hepatocellular carcinoma cell line MHCC97-H and MHCC97-L with lower metastatic potential using miRNA microarrays. By quantitative real-time PCR, we confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 32 publications
2
22
0
1
Order By: Relevance
“…Overexpression of ST3GAL5 significantly promoted the proliferation and invasion of hepatoma cells. In contrast, knockdown of ST3GAL5 inhibited proliferation and metastasis of hepatoma cells [47].…”
Section: Discussionmentioning
confidence: 90%
“…Overexpression of ST3GAL5 significantly promoted the proliferation and invasion of hepatoma cells. In contrast, knockdown of ST3GAL5 inhibited proliferation and metastasis of hepatoma cells [47].…”
Section: Discussionmentioning
confidence: 90%
“…Following hybridization, the slides were washed several times using a Wash Buffer Kit (Exiqon). The slides were scanned using an Axon GenePix 4000B Microarray Scanner (Axon Instruments, Foster City, CA, USA) [20]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition to studies that have evaluated the role of miR-34a alone in cancer pathogenesis, there are some reports that have evaluated the functional involvement of multiple miRNAs in cancer progression and/or therapy, with miR-34a being a part of the miRNA panel. For example, ST3 Beta-Galactoside Alpha-2,3-Sialyltransferase 5 (ST3GAL5), a sialyltransferase gene, has been shown to be directly targeted by miR-34a, miR-548l, and miR-26a [ 42 ]. Overexpression of miR-34a, miR-548l, and miR-26a in MHCC97-L or MHCC97-H cells substantially changed their malignant behaviors and oncogenicity.…”
Section: Mir-34a Co-operates With Multiple Micrornas To Target Difmentioning
confidence: 99%
“…Overexpression of miR-34a, miR-548l, and miR-26a in MHCC97-L or MHCC97-H cells substantially changed their malignant behaviors and oncogenicity. The size and weight of tumors were notably reduced in mice inoculated with miR-34a, miR-548l, and miR-26a, and miR mixture mimics groups [ 42 ]. Data clearly suggested that miR-34a in combination with different tumor suppressor miRNAs negatively regulated ST3GAL5 to inhibit hepatocellular carcinoma.…”
Section: Mir-34a Co-operates With Multiple Micrornas To Target Difmentioning
confidence: 99%